Vortex shedding lock-in of a 2-D wind turbine blade section at high angles of attack - Pellegrino, Alberto (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2015)
The vortex shedding behaviour of a 2-D wind turbine blade section at high angles of attack (a = [35° —>145°]) has been investigated using unsteady RANS with the transition SST turbulence model. The Reynolds number is Re = 10(6) based on a chord length of 1m. The airfoil examined is the NREL S809 (Phase-VI).
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin